2012
DOI: 10.1038/nprot.2012.057
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)/TEMPO-catalyzed aerobic oxidation of primary alcohols to aldehydes with ambient air

Abstract: This protocol describes a practical laboratory-scale method for aerobic oxidation of primary alcohols to aldehydes, using a chemoselective CuI/TEMPO catalyst system. The catalyst is prepared in situ from commercially available reagents, and the reactions are performed in a common organic solvent (acetonitrile) with ambient air as the oxidant. Three different reaction conditions and three procedures for the isolation and purification of the aldehyde product are presented. The oxidations of eight different alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
115
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(115 citation statements)
references
References 30 publications
(24 reference statements)
0
115
0
Order By: Relevance
“…PPh 3 reduces CyOOH to CyOH, resulting in an increase in the alcohol amount and a decrease in that of CyO. This behavior has been observed in several peroxidative oxidation systems [2(h),2(r),3(g), 11,12].…”
Section: Resultsmentioning
confidence: 86%
“…PPh 3 reduces CyOOH to CyOH, resulting in an increase in the alcohol amount and a decrease in that of CyO. This behavior has been observed in several peroxidative oxidation systems [2(h),2(r),3(g), 11,12].…”
Section: Resultsmentioning
confidence: 86%
“…11 Recent progress indicates that both Cu(I) and Cu(II) complexes with a N,N-or N,O-ligands in combination with TEMPO could be efficient catalysts or catalyst precursors for the aerobic oxidation of various alcohols, and of particular note is a highly efficient copper/2,2'-bipyridine/TEMPO system developed by the Stahl group. [12][13][14][15][16][17] However, the types of organic ligands exploited in the copper catalyst systems are still limited and the structures of copper catalysts involved in the catalytic process are rarely explored. [17][18][19][20] The construction of metal-organic cluster compounds through self-assembly of predesigned ligands with appropriate metal ions is a prime research topic [21][22][23][24][25] due to the advantages in catalysing useful chemical transformations, in contrast to simple monometallic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In 1984, Semmelhack and co-workers carried out a copper-catalyzed, 2,2,6,6-tetramethylpiperidinyl-1-oxyl(TEMPO)-mediated aerobic oxidation of primary alcohols by using a simple Cu I Cl/TEMPO system in DMF (N,N-dimethylformamide) [21], and thereafter, a variety of Cu/TEMPO methodologies has been extensively developed for the aerobic oxidation of a range of aromatic and aliphatic primary alcohols by the Sheldon, Koskinen and Stahl groups [18,19,[22][23][24][25][26]. Amongst some efficient copper-based catalyst systems reported so far, a N,Nbidentate ligand was often employed as a reactivity promoter, this includes 2,2′-bipyridine (bpy), 1,10-phenanthroline and 1,4-diazabicylo [2,2,2]octane with bpy remaining the most popular choice [23][24][25][26].Except for the N,N-type ligands that were extensively investigated, N,O-chelating ligands have also been found to be suitable ligand candidates for this reaction, although such examples were only little reported [27][28][29][30][31]. The Punniyamurthy group reported that a salen-type N,Oligand promoted efficient oxidation of primary alcohols to aldehydes under oxygen conditions [27].…”
mentioning
confidence: 99%
“…In contrast to some precious metal catalysts such as Pd II , Ru II and Ir II that were developed in the past few years [12][13][14][15][16], earth-abundant and inexpensive Cu II has recently attracted more attention, owing to its great potential as precious metal surrogate for catalysis in large-scale industrial applications [17][18][19][20]. In 1984, Semmelhack and co-workers carried out a copper-catalyzed, 2,2,6,6-tetramethylpiperidinyl-1-oxyl(TEMPO)-mediated aerobic oxidation of primary alcohols by using a simple Cu I Cl/TEMPO system in DMF (N,N-dimethylformamide) [21], and thereafter, a variety of Cu/TEMPO methodologies has been extensively developed for the aerobic oxidation of a range of aromatic and aliphatic primary alcohols by the Sheldon, Koskinen and Stahl groups [18,19,[22][23][24][25][26]. Amongst some efficient copper-based catalyst systems reported so far, a N,Nbidentate ligand was often employed as a reactivity promoter, this includes 2,2′-bipyridine (bpy), 1,10-phenanthroline and 1,4-diazabicylo [2,2,2]octane with bpy remaining the most popular choice [23][24][25][26].…”
mentioning
confidence: 99%
See 1 more Smart Citation